Graphene quantum dots with multi-band emission: Unraveling the molecular origin of graphene quantum dots - Shedeed, Radwa Adel (AUC Knowledge Fountain, 2017)
Graphene quantum dots (GQDs) have grasped the attention of researchers from many fields, mainly due to their unique optoelectronic properties. These properties made GQDs of potential use in various applications, such as photocatalysis, optoelectronics, bioimaging, solar cells, sensors, and surface-enhanced Raman scattering. However, the dependence of their fluorescence spectra on the excitation wavelength has been the focus of several recent studies. While some studies attributed their multi-chromophoric behavior to core and surface states, others related it to the differently-sized nanodomains of sp2-hybridized carbon in an amorphous matrix. Herein, colloidal GQDs were directly synthesized via low-temperature catalytic chemical vapor deposition (CVD). These graphene nanostructures were found to exhibit well-resolved multi-emission bands in the visible region. Based on the X-ray photoelectron, FT-IR and Raman spectroscopies, as well as density functional theory (DFT) calculations, the role of polycyclic aromatic hydrocarbons (PAHs), was identified as the building blocks of GQDs. Also, the fluorescence spectra of GQDs thin films were investigated. Moreover, the effect of plasmonic nanomaterials, such as silver nanodisks (AgNDs), on their fluorescence was investigated. A Polyvinylpyrrolidone (PVP) polymer is used as a dielectric material to prevent the diffusion of the AgNDs particles in the GQDs layer and minimize the quenching effect. Different four concentrations of GQDs were used (0.2%, 1%, 3% and 5%) to get the optimum conditions of GQDs/spacer/AgNDs hybrid-nanomaterial. The 1% weight concentration of GQDs shows the optimum fluorescence emission of GQDs/spacer/AgNDs composite.